The Role of Rho/Rho-Kinase Pathway in the Pathophysiology of Absence Epilepsy - ONAT, FİLİZ (KARE PUBL, 2018)
Objectives: Rho/Rho-kinase (ROCK) signaling has been shown to contribute to neuroinflammation, epileptogenesis, and seizures in convulsive-type epilepsy models. However, this pathway has not been investigated in the pathophysiology of absence epilepsy. The aim of this study was to investigate ROCK activity in brain regions involved in spike-and-wave discharge (SWD) generation and the effects of the Rho-kinase inhibitor, Y-27632, on ROCK activity in genetic absence epilepsy rats from Strasburg (GAERS). Methods: ROCK activity in the somatosensorial cortex, hippocampus, and thalamus was measured using an enzyme-linked immunosorbent assay (ELISA). An intracerebroventricular (i.c.v.) injection of Y-27632 was administered at a dose of 20 nmol/5 mu l and changes in ROCK activity were assessed. To evaluate the effect of Y-27632 on SWDs, i.c.v. 20 nmol and 60 nmol doses of Y-27632 were administered to the GAERS subjects and electroencephalography was performed. Results: ROCK activity was elevated in the somatosensory cortex in the GAERS study subjects, and the Rho-kinase enzyme inhibitor, Y-27632, suppressed this increase. In addition, Y-27632 significantly reduced the total and mean duration of SWDs compared with the control group. Conclusion: The findings indicate that the Rho-kinase pathway may play a role in the generation of absence seizures, and that the suppressive effect of Y-27632 on SWDs may be a potential therapeutic target for this anti-absent effect.
Keywords: Absence epilepsy; enzyme-linked immunosorbent assay; Rho/Rho-kinase; Rho-kinase; genetic absence epilepsy rats from Strasburg; Y-27632; KAPPA-B INHIBITION; RHO-KINASE; SOMATOSENSORY CORTEX; NETWORK MECHANISMS; CORTICAL-NEURONS; WAVE DISCHARGES; ROCK INHIBITOR; VALPROIC ACID; GENETIC MODEL; RAT MODEL